دور الاقتصاد المبني على المعرفة في زيادة تنافسية القطاع الصناعي في سورية (Latakia University Journal - Economic and Legal Sciences Series, 2013)
إن التحولات التي أصابت الاقتصاد العالمي وخاصة في التسعينيات من القرن العشرين، أسهمت بشكل كبير في نشوء وتكوين الاقتصاد المبني على المعرفة. وأصبح الاقتصاد المبني على المعرفة الشغل الشاغل لدول العالم ومحرّكاً قوياً للتحولات الاقتصادية والاجتماعية ,لأنه قائم على المزج بين النظام الاقتصادي والاجتماعي المعاصر، وبين التجربة العالمية الناجحة مع الخبرة الوطنية، لتوفير منتجات ذات قيمة مضافة عالية, وإعداد أفراد مؤهلين. وترافق مع  تكوين الاقتصاد المبني على المعرفة , العمل على تنظيم وحدات الاقتصاد الكلي لإدخال اقتصاد المعرفة في مختلف نشاطاته في المجتمع، في سبيل إنشاء بيئة ملائمة تضمن توليد المعرفة ونشرها وتوظيفها والاستفادة منها، بما يساعد على تحويل الأفكار إلى إعمال ابتكاريه وإبداعية في مجال الإستثمار في المعرفة والمعلومات من أجل تحسين واقع القطاع الصناعي في سورية التي هي في أمس الحاجة إلى استخدام التكنولوجيا وتطبيقات  الاقتصاد المبني على المعرفة في مجال رفع تنافسية القطاع الصناعي لأنه يعدّ قاطرة التنمية للوصول إلى مستوى الدول الصناعية المتقدمة في العالم. The transformations that have affected the global economy, especially in the nineties of the twentieth century contributed significantly to the evolution and composition of the knowledge economy and become a knowledge based economy,become the main concern for the world and a powerful engine of economic and social transformations because it is based on a combination of the contemporary economic and social system of, and the successful global national to provide products with high added value, and the preparation of qualified personnel. Accompanied by formation knowledge economy, to work on the organization of units macroeconomic to enter the knowledge-based economy in the various activities in the community, in order to create a favorable environment to ensure generation and dissemination of knowledge and employ them and take advantage of them, that help transform ideas into realization of innovative and creative in the field of investment in knowledge and information in order to improve the reality of the industrial sector in Syria, which is in dire need to use technology and applications of knowledge-based economy in raising the competitiveness of the industrial sector because it is considered locomotive development, to reach the level of the advanced industrial countries in the world.